Effect of Glycemic Parameters on Mortality of Type 2 Diabetes Mellitus Patients with COVID-19 Infection in Haji Adam Malik Hospital Medan - Pangaribuan, Jessica Patricia; Syafril, Santi; Lubis, Dian Anindita; Isnanta, Rahmad; Rey, Imelda (Journal of Society Medicine, 2023)
Introduction: Diabetes Mellitus Type 2 (DM T2) is a major health problem, especially in people in developing countries. DM T2 is the most frequently reported comorbid disease in patients with COVID-19. The relationship between DM T2 and poorer outcome in COVID-19 infection is thought to be because hyperglycemia and chronic inflammation impair control of viremia and inflammation by weakening the immune response. This research aim to determine the effect of glycemic parameters on the mortality of DM T2 patients with COVID-19. Method: This research is a descriptive analytic study with a retrospective design which was carried out at the H. Adam Malik General Hospital in Medan. The data obtained was analyzed statistically and said to be statistically significant if p <0.05. Results: Based on the results of the study, there were significant differences in the values of inflammatory markers such as leukocytes, neutrophils, NLR, PCT, LDH, D-dimer, ferritin, SGOT, urea and creatinine in the severity of COVID-19 patients and there were significant differences in the mean fasting blood sugar, blood sugar 2PP, in moderate, severe and critical COVID-19 patients. Conclusion: Glycemic parameters in patients who died were worse than patients who recovered, although the statistical results were not significantly different.